Macrofauna Diversity of Molluscs (Gastropoda and Polecypoda) Associated with Mangrove in the Coastal Area of South Cemara Sheet Beach, West Lombok - Karima Paspania; Abdul Syukur; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cedar Beach is a tourist attraction with a unique mangrove forest, opened in 2015 by the Maritime Affairs and Fisheries Service together with the South Sheet Village. Macro fauna is a group of large animals that live in the soil or water and have an important role in improving the physical, chemical and biological properties of the surrounding environment. Research on the diversity of molluscs (Gastropoda and Polecypoda) was conducted to determine the type, diversity, and relationship between Molluscs (Gastropoda and Polecypoda) and Mangrove. The number of individual Gastropods and Polecypods found in the mangrove area of the Cypress Beach is 9 species of Gastropods and 4 species of Polecypods. Diversity of Gastropods found in the mangrove area of Pantai Cemara was 1,009 in the moderate category, 0,405 in the diversity of Polecypoda was found in the low category, and mangrove diversity was categorized as moderate. The correlation between the diversity of Gastropods, Polecypoda and mangrove diversity is not significant because the environmental parameter value is salinity at the study site above 35 ppm which has a negative impact on mangroves due to negative osmotic pressure.